The Dominant Role of After-Sales Service Quality in Driving Purchase Satisfaction for Industrial Investment Products - Nanlohy, Grishella (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This research examines the influence of Instagram Content, Price, and Service Quality on Purchase Satisfaction of the generator at PT. Suryaindo Makmur Teknik (Simtek Power). This topic is important because it analyzes the relative contribution of digital marketing elements versus traditional factors (Price and Service) in the context of investment product (B2B) decision-making. Background Problems: In the context of industrial products, there is ambiguity regarding the most dominant predictors of Purchase Satisfaction. This study aims to answer the question: To what extent do Instagram Content, Price, and Service significantly affect Simtek Power’s customer Purchase Satisfaction? This quantitative research :P research uses a causal-comparative design. Data was collected through an online questionnaire from 118 Simtek Power customers using purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test measurement models and structural models. Finding/Results: Empirical results show that Services (ß= 0.583; p = 0.000) have a positive and significant effect on Purchase Satisfaction, making it the most dominant predictor. In contrast, Instagram Content and Price have no significant influence on Satisfaction. These findings indicate that the Purchase Satisfaction of investment products is dominated by the after-sales experience and reliability of the Service, not the pre-purchase aspect (digital or cost). Conclusion: The conclusion of this study confirms that in the purchase of investment products, Service Quality is a key and strategic factor that determines customer satisfaction. The implications of the study suggest Simtek Power to prioritize resource allocation on improving after-sales support and adapt digital content strategies to support a narrative of service excellence, rather than competing through price.